Sleep and Sleep Disorders in Rare Hereditary Diseases: A Reminder for the Pediatrician, Pediatric and Adult Neurologist, General Practitioner, and Sleep Specialist - Gadoth, Natan; Oksenberg, Arie (Frontiers in Neurology, 2014)
Although sleep abnormalities in general and sleep related breathing disorders (SBD) in particular are quite common in healthy children, their presence is notably under-recognized. Impaired sleep is a frequent problem in subjects with Inborn Errors of Metabolism (IEM) as well as in a variety of genetic disorders; however, they are commonly either missed or underestimated. Moreover, the complex clinical presentation and the frequently life threatening symptoms are so overwhelming that sleep and its quality may easily dismissed. Even centers which specialize in rare genetic-metabolic disorders are expected to see only few patients with a particular syndrome, a fact that significantly contributes to the under-diagnosis and treatment of impaired sleep in this particular population. Many of those patients suffer from reduced life quality associated with a variable degree of cognitive impairment which may be worsened by poor sleep and abnormal ventilation during sleep, abnormalities which can be alleviated by proper treatment. Even when such problems are detected, there is a paucity of publications on sleep and breathing characteristics of such patients that the treating physician can refer to. In the present paper we provide an overview of sleep and breathing characteristics in a number of rare genetic-metabolic disorders with the hope that it will serve as a reminder for the medical profession to look for possible impaired sleep and SBD in their patients and when present to apply the appropriate evaluation and treatment options .